2021
DOI: 10.1007/s00432-021-03521-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of cardiovascular risks among nine FDA-approved VEGFR-TKIs in patients with solid tumors: a Bayesian network analysis of randomized controlled trials

Abstract: Purpose The present meta-analysis study was performed to identify the potential cardiotoxicity risks when using Vascular Endothelial Growth Factor Receptor Tyrosine kinase inhibitors (VEGFR-TKIs) as anticancer drugs in patients with solid tumors. Methods Pubmed, Embase, the Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov databases were searched for the randomized controlled trials. We have included 45 randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
(33 reference statements)
2
24
0
Order By: Relevance
“…Lenvatinib is a small molecule tyrosine kinase inhibitor and clinically used for the treatment of radio‐iodide refractory differentiated thyroid cancer and other cancers. Related clinical reports suggested that lenvatinib had a serious risk of hypertension and cardiotoxicity, with mitochondrial toxicity in H9c2 cardiomyoblastic cell line exposed to lenvatinib 18–21 . With the increasing clinical use of lenvatinib, the effects of the parent and its metabolites discharged into the water on non‐target organisms should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lenvatinib is a small molecule tyrosine kinase inhibitor and clinically used for the treatment of radio‐iodide refractory differentiated thyroid cancer and other cancers. Related clinical reports suggested that lenvatinib had a serious risk of hypertension and cardiotoxicity, with mitochondrial toxicity in H9c2 cardiomyoblastic cell line exposed to lenvatinib 18–21 . With the increasing clinical use of lenvatinib, the effects of the parent and its metabolites discharged into the water on non‐target organisms should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Related clinical reports suggested that lenvatinib had a serious risk of hypertension and cardiotoxicity, with mitochondrial toxicity in H9c2 cardiomyoblastic cell line exposed to lenvatinib. [18][19][20][21] With the increasing clinical use of lenvatinib, the effects of the parent and its metabolites discharged into the water on non-target organisms should be taken into account. Here, we used zebrafish embryos to evaluate its cardiovascular effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe adverse events due to high plasma concentrations of TKIs may be also addressed by the application of TDM-guided dosing, ensuring levels within the therapeutic window [ 112 ]. Particularly relevant on this issue is the very recent meta-analysis by Hou et al performed to identify the potential cardiotoxicity risks of VEGFR–TKIs in patients with solid tumors [ 113 ]. These authors concluded that among the VEGFR–TKIs, lenvatinib and vandetanib revealed the highest possibility to provoke cardiovascular events and hypertension, followed by cabozantinib, axitinib, pazopanib, sorafenib, sunitinib, regorafenib, and nintedanib.…”
Section: Discussionmentioning
confidence: 99%
“…FDA approved VEGFR-TKIs for Kidney Cancers (Jeong et al, 2013;Roskoski, 2022) RCC: Renal Cell Carcinoma VEGFR-TKIs block VEGFR activation (mediated by VEGFs) and thus they inhibit angiogenesis and tumor cell growth. Although good results have been obtained in the treatment of RCC and other tumors with VEGFR-TKIs, adverse effects caused by them such as hypertension and cardiovascular damage and the development of drug resistance remain serious clinical problems (Pandey et al, 2018;Erman et al, 2021;Hou et al, 2021;Sharma et al, 2021). Hou et al (2021) reported that the degree of cardiotoxic risk differed between VEGFR-TKIs, and Lenvatinib has been associated with the highest probability of producing all degrees of cardiovascular injury and hypertension.…”
Section: Table 1 Vegfrs In Humansmentioning
confidence: 99%
“…Although good results have been obtained in the treatment of RCC and other tumors with VEGFR-TKIs, adverse effects caused by them such as hypertension and cardiovascular damage and the development of drug resistance remain serious clinical problems (Pandey et al, 2018;Erman et al, 2021;Hou et al, 2021;Sharma et al, 2021). Hou et al (2021) reported that the degree of cardiotoxic risk differed between VEGFR-TKIs, and Lenvatinib has been associated with the highest probability of producing all degrees of cardiovascular injury and hypertension. Natural non-toxic compounds targeting VEGFRs might be an alternative to VEGFR-TKIs to reduce such adverse effects.…”
Section: Table 1 Vegfrs In Humansmentioning
confidence: 99%